Changes in fan gratifications and sports media dependency after the postponement of sports due to the COVID-19 pandemic - O'Brate, Shawn (Kansas State University, 2021)
Throughout most of written history, there has been a fascination for sports, from gladiator fights to the first Olympic Games, which has turned into a form of dependence worldwide. Today, a bevy of professional sports and a plethora of professional teams fill stadiums, television slots, and streaming sites. With every sport comes fans, and with every fan comes an assortment of reasons as to why they are fans of certain sports, teams or athletes. Most of these fans use sports as an escape from under-stimulation (i.e., boredom, apathy) as well as over-stimulation (i.e., stress and anxiety) in their daily lives (Wann, Allen & Rochelle, 2004). Some fans, especially those heavily dedicated to specific teams, may even consider their sport or team a religion of sorts (Price, 2005). What would a typical fan do if all sports were taken away from them quickly and without warning? How would fans react if their favorite team was suddenly unable to participate in playoffs or championship? That is exactly what happened in March of 2020 because of growing concern about COVID-19. This thesis explores how the average sports fans and fantasy sports fans spent their time quarantining without their beloved sports, and it examines how dependent the common fans are on sports and sports media before, during, and after being forced to remain at home without any new games or matches for months on end.
Keywords: Media dependency; Uses and gratifications theory; Fan identification; Sports media; Coronavirus; COVID-19